OF SOME FIELD TRAITS OF WHEAT TO ABA UNDER EFFECT OF WATER STRESS RESPONSE - & Ahmed, Hashim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Two field experiments were carried out at the field crop research station- Abu-Ghraib of agricultural researches office during 2014-2015 and 2015-2016 to investigate effect of water irrigation quantities and ABA concentrations soaking and spraying on some morphological traits of wheat cultivar bahooth 10. Split plot arrangement by RCBD with three replicates for each experiment. First trial included for water irrigation volumes which control treatment (irrigation 50% of the water available), 70% and 40% from control treatment as well as rainy treatment (germination irrigation + rainfed) which occupied main plots while ABA soaking concentration (0, 1, 2, and 3) micromoles which occupied sub plots. Second experiment included same irrigation treatments which occupied main plots while ABA spraying concentration (0, 30, 60 and 90) micromoles occupied sub plots. Irrigation treatment 70% of first experiment produced plant height was 97.08 cm and flag leaf area 46.35 cm-2 and dry weight at 100% anthesis 1144.57 gm m-2. For second experiment control treatment gave highest values for duration from planting to 100% anthesis 113.41 and 111.50 day, number of tillers 388.95 and 403.18 tiller m-2 , the crop growth rate 10.61 and 11.31 g m-2 day for both season respectively with no significant difference with 70% of control treatment for both seasons. Soaking concentration 3 micromoles attained the highest value of number of tillers 338.58 and 354.20 tiller m-2, dry matter at 100% anthesis 970.10 and 1102.43 gm m-2, day the crop growth rate 8.85 and 10.16 gm-2 . day for both seasons respectively .While spraying 90 micromoles concentration gave the lowest values for plant height 82.63 and 88.22 cm, but the highest value for number of tillers 336.67 and 384.92 tiller m-2 , for both season , day the crop growth rate 9.13 and 9.05 g m-2 day for first season with did not differ significantly from 60 micromoles . Therefore could be conclude to capability of irrigation with 70% from full irrigation without signification effect in growth traits, as well as can be treat plant wheat with ABA concentration 3 and 60 micromoles soaking and spraying respectively to improve their ability to tolerance water stress .